White Matter Abnormalities in Cervical Dystonia - Shibanova, Mariia (My University, 2023)
Background: Cervical dystonia is a neurological condition involving involuntary neck muscle contractions and abnormal postures. Previous studies have suggested that cervical dystonia is associated with brain white matter structural abnormalities in various brain regions, however the results across the studies are not consistent. Objective: Investigate brain white matter microstructural abnormalities in cervical dystonia patients using diffusion-weighted MRI and Tract-Based Spatial Statistics (TBSS). Methods: Data from thirteen subjects with cervical dystonia and fifteen healthy controls were analyzed. Fractional anisotropy and mean diffusivity maps were created and analyzed, controlling for age and gender using a general linear model. Results: Subjects with cervical dystonia showed a significant decrease in fractional anisotropy values (p<0.05, TFCE-corrected) compared to healthy controls. Voxels containing significant difference were found in such brain regions as the right retrolenticular part of the internal capsule, right posterior thalamic radiation, right sagittal stratum (including inferior longitudinal fasciculus and inferior fronto-occipital fasciculus), right external capsule, right fornix, and right putamen. No significant difference was detected in mean diffusivity values between the two groups. Conclusion: Our study revealed significant differences in white matter microstructure between individuals with cervical dystonia and healthy controls, supporting the presence of microstructural abnormalities in cervical dystonia. These findings align with previous research, highlighting cervical dystonia as a network disorder with multiple brain regions affected. Additionally, this study reported about less commonly observed regions in cervical dystonia, underscoring the importance of further investigation. Therefore, our study offers valuable insights into the understanding of microstructural abnormalities and the brain regions potentially involved in the pathophysiological mechanism of cervical dystonia, providing a foundation for further investigations in this area.
Keywords: Cervical Dystonia, Diffusion Tensor Imaging